Clinical experience using the iodophorm and camphora paste in the treatment of chronic apical periodontitis (LLC "Endo Press", 2020)
The article presents clinical cases using iodoform and camphora paste in the treatment of chronic apical periodontitis. The aim of the study was to analyze the effectiveness of Iodoform Paste (PD) for temporary obturation of the root canals in patients with destructive changes in the periapical area. The results of the study proved that the acceptance of iodoform and camphora paste for temporary obturation of the root canals helps to reduce the focus of bone tissue destruction.